2010
DOI: 10.1126/science.1194174
|View full text |Cite
|
Sign up to set email alerts
|

Impeding Xist Expression from the Active X Chromosome Improves Mouse Somatic Cell Nuclear Transfer

Abstract: Cloning mammals by means of somatic cell nuclear transfer (SCNT) is highly inefficient because of erroneous reprogramming of the donor genome. Reprogramming errors appear to arise randomly, but the nature of nonrandom, SCNT-specific errors remains elusive. We found that Xist, a noncoding RNA that inactivates one of the two X chromosomes in females, was ectopically expressed from the active X (Xa) chromosome in cloned mouse embryos of both sexes. Deletion of Xist on Xa showed normal global gene expression and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
297
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(320 citation statements)
references
References 18 publications
19
297
3
1
Order By: Relevance
“…This is because epigenetic mechanisms ensuring the stability of the differentiated state confer a resistance to these reprogramming activities of the egg and oocyte 74 . Indeed, nuclear transfer can be improved by interfering with the epigenetic state of the donor nuclei, for example their DNA methylation and histone acetylation levels or their expression of noncoding RNAs [63][64][65] . One can speculate that the eggs and oocytes are not fully equipped to reverse the effects of specific components that restrict nuclear plasticit y, especially in highly differentiated cells…”
Section: Deterministic or Stochastic?mentioning
confidence: 99%
“…This is because epigenetic mechanisms ensuring the stability of the differentiated state confer a resistance to these reprogramming activities of the egg and oocyte 74 . Indeed, nuclear transfer can be improved by interfering with the epigenetic state of the donor nuclei, for example their DNA methylation and histone acetylation levels or their expression of noncoding RNAs [63][64][65] . One can speculate that the eggs and oocytes are not fully equipped to reverse the effects of specific components that restrict nuclear plasticit y, especially in highly differentiated cells…”
Section: Deterministic or Stochastic?mentioning
confidence: 99%
“…De manière plus générale, un contenu riche en ARN et en protéines d'origine maternelle est hérité après la fécondation de l'ovocyte (voir note 1) et pourrait donc être impliqué, au moins pendant les premières divisions mitotiques, dans l'expression de l'allèle paternel Xist. En effet, des expériences de clonage somatique ont démontré que ce gène pouvait être activé à partir des deux copies d'une cellule d'origine maternelle ou bien à partir de la copie unique d'une cellule mâle (XY) [16]. Ceci démontre que les activateurs de Xist sont présents par défaut dès la fécondation.…”
Section: Inactivation Du Chromosome X Soumise à Empreinteunclassified
“…7 In mice, analysis of female SCNT-derived embryos for the Xist expression pattern and XCI-specific markers have shown that both X chromosomes were inactivated by ectopic Xist expression. [8][9][10] It has also been reported that Xist is expressed from only the X chromosome in male SCNT embryos. 10 Intriguingly, this SCNT-associated perturbation is autonomously corrected after implantation in both embryonic and extraembryonic lineages of both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] It has also been reported that Xist is expressed from only the X chromosome in male SCNT embryos. 10 Intriguingly, this SCNT-associated perturbation is autonomously corrected after implantation in both embryonic and extraembryonic lineages of both sexes. 11,12 A series of experiments using gene knockout and knockdown strategies During mouse development, imprinted X chromosome inactivation (XCi) is observed in preimplantation embryos and is inherited to the placental lineage, whereas random XCi is initiated in the embryonic proper.…”
Section: Introductionmentioning
confidence: 99%